Child monitoring device using low frequency RF tagging - Liboro, Joseph Patrick Y. (2003)
A working prototype of a Low Frequency RF Tagging System was designed and implemented. The limitless application of RF Tagging was shown by using the system as a low cost Child Monitoring Device. The Tag is worn by the child and is detected when it has passed through the surveillance zone. The RF Tagging System transmits a swept signal varying from 200-300khz that includes the resonance frequency of the tag. A tag's presence is translated to voltage signals which triggers the alarm. The system requires only one antenna to transmit and detect a tag. The tag which resonates at a frequency of 264khz, is a simple capacitor and inductor connected in parallel.
Thesis (B.S. E.C.E.)--University of the Philippines Diliman.
Keywords: Radio frequency; RF tagging; Child monitoring device